THE IMPORTANCE OF MIND MAPPING TECHNIQUE IN THE EFL CLASSROOM: Today's world requires each individual to be very active and creative. - Kalimbetova, Kizlargul (Журнал иностранных языков и лингвистики, 2025)
Today's world requires each individual to be very active and creative. Rapid changes in society require the curriculum and teaching methodology to be changed, updated and to a have positive effect on society. Effective learning and idea organization techniques have become essential for academic and professional success. One such technique gaining popularity for its visual and cognitive appeal is Mind Mapping.